Alpha – amylase enzyme evaluation In Saliva of acutely stressed student (Mustansiria Dental Journal, 2018)
Alpha - amylase is one of the major protein components of saliva. The mainfunction of salivary alpha-amylase is the enzymatic digestion of carbohydrates, but itis also important for mucosal immunity in the oral cavity. The salivary enzyme alphaamylasehas been proposed as a marker for stress-induced activity of the sympatheticnervous system. In the growing field of amylase research, recent studies haveunderscored the usefulness of salivary alpha-amylase in this regard.Fifteen Iraqi male students were considered in this study with mean age of 19.0years old during examination period as stress students, another fifteen studentswithout examination were considered as .control. α-Amylase assay were achieved byusing colorimetric photometry method.The collected data predicted elevation of amylase level from 2354.260 ± 379.757to 2817.977 ± 125.375 IU/L with a significant change. Positive correlationwas recorded when plotted the correlations values of stress and no stress individual's.In Conclusion we found that acute stress caused by examination associated withelevation of amylase in saliva significantly, however one of the main causes ofacademic stress is test anxiety for Undergraduate students seem to be moreemotionally vulnerable due to examinations.